Revival of Private Participation in Developing Country Infrastructure - Kerf, Michel (World Bank, Washington, DC, 2012)
Investment in private participation in infrastructure projects in developing countries in 2004 and 2005 increased sharply. Meanwhile, the distribution of investment across sectors and regions, and the allocation of risks between public and private parties, were shifting. Private sponsors started putting more emphasis on risk mitigation strategies. To take advantage of private sponsors' renewed interest in infrastructure projects, governments need to create risk sharing arrangements that attract private operators while also benefiting governments, taxpayers, and users.